A Soft Anthropomorphic & Tactile Fingertip for LowCost Prosthetic & Robotic Applications - Secco, E. L.; Moutschen, C. (EAI Endorsed Transactions on Pervasive Health and Technology, 2018)
Nowadays, prosthetic and robotic hands have reached an amazing dexterity and grasping capability. However, to enhance a proper tactile ’experience’, dexterity should be supported by proper sensation of daily life objects which such devices are supposed to manipulate. Here we propose a low cost anthropomorphic solution for the integration of a force sensor within a biologically inspired fingertip. A commercial force resistive sensor is embedded within a human-like soft fingertip made of silicone: the housing of the sensor - a 3D printed bay embedded within the fingertip - is analyzed via Finite Element Analysis and optimized to enhance sensor response. Experiments validate the design and proposed solution.